An enzyme-assisted self-delivery system of lonidamine–peptide conjugates for selectively killing cancer cells. Issue 98 (26th November 2019) - Wu, Can; Liu, Jing; Tang, Xuan; Zhai, Ziran; Xu, Keming; Zhong, Wenying
Abstract : A self-delivery system consisting of lonidamine and a self-assembling peptide was designed for the selective killing of phosphatase-overexpressing cancer cells. Abstract : A self-delivery system consisting of lonidamine and a self-assembling peptide was designed for the selective killing of phosphatase-overexpressing cancer cells, which was mediated by both enhanced cellular uptake of LND–peptide and enzyme-triggered intracellular fiber formation, thereby providing a generalized strategy to develop cancer-targeting systems of drug conjugates.